Choking at Night: A Case of Opercular Nocturnal Frontal Lobe Epilepsy - Geetanjali Rathore; Paul Larsen; Manish Parakh; Cristina Fernandez (Hindawi Limited, 2013)
Frontal lobe seizures have a tendency to occur in sleep and in most cases occur exclusively insleep; these individuals are said to have nocturnal frontal lobe (NFLE). NFLE can be difficult to distinguish clinically from various other sleep disorders, particularly parasomnias, which also present with paroxysmal motor activity in sleep. Interictal and ictal EEG findings are frequently unremarkable or nonspecific in both parasomnias and NFLE making the diagnosis even more difficult. Nocturnal epilepsy should be suspected in patients with paroxysmal events at night characterized by high frequency, repetition, extrapyramidal features, and marked stereotypy of attacks. Here we present a 13-year-old female who was extensively worked up for choking episodes at night. On repeat video EEG she was found to have frontal opercular seizures. Once on Carbamazepine, her seizures completely resolved.